Comparison of transanal Hemorrhoidopexy versus laser hemorrhoidoplasty with digital-guided hemorrhoidal artery ligation - Rajkumar Verma; Prashant Kumar; Pooja Prajapati (Asian Journal of Medical Sciences, 2024)
Background: Hemorrhoids are a common proctological disease that affects the quality of life in the patient population to a great extent. Nearly 4.4–36% of population is affected by hemorrhoids. The symptoms of hemorrhoids vary from painless bleeding to embarrassing and painful prolapsing mass. Aims and Objectives: Comparison of transanal hemorrhoidopexy versus laser hemorrhoidoplasty with digital-guided hemorrhoidal artery ligation in treatment of grade III and grade IV hemorrhoids. Materials and Methods: The study was conducted on 50 cases of transanal hemorrhoidopexy and 50 cases laser hemorrhoidoplasty in Maharani Laxmi Bai Medical College, Jhansi between January 2021 and June 2022. Results: Out of 50 cases of transanal hemorrhoidopexy, post-operative pain at 6 h was 2.02±0.795, at 12 h was 4.86±0.606, and at 24 h was 2.36±0.525 and 50 cases of laser hemorrhoidoplasty with Doppler-guided hemorrhoidal artery ligation (DGHAL) at 6 h was 1.1±0.303, at 12 h was 1.78±0.648, and at 24 h was 108±0.274. Mean hospital stay was 2.28±0.573 days in transanal hemorrhoidopexy and 1.12±0.328 days in laser hemorrhoidoplasty with DGHAL. Mean return to work in transanal hemorrhoidopexy was 7.422±1.071 days and in laser hemorrhoidoplasty with DGHAL was 3.2±0.80 days. Conclusion: Laser hemorrhoidoplasty with digital-guided hemorrhoidal artery ligation procedure significantly reduced duration of hospital stay, duration of return to work, and post-operative pain as compared to open transanal hemorrhoidopexy.